(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2017)
Consistent "with the thought of tax talk is unified tax natural evolution for him, as the application leads to the inclusion of tax all branches of income and its sources and through truncated part of this entry through the application of price ascending it, it means the procedures of tax reform. Taxes on total income characterized by giving a clear picture of the total income of the taxpayer and its financial situation and its burden family which allows granting exemptions, downloads, and application of prices that fit this case. This requires reconsideration of the structure of the tax system in force and the transition from a system specific taxes to the tax system on the total income of the integration of income from the rental of real estate, as well as taxes on vacant land with other sources of income obtained by the taxpayer in a uniform tax into line "so the majority of modern tax legislation in the countries of the world. The research on the importance of the introduction of unified tax including features framework simplified procedures and improve the mechanism of action and re-engineering work so that it is capable of "management by mechanization., Where he plays technological advances play a key role in improving the completion of transactions tax by relying on ID Consolidated Per expensive that demonstrates all personal information and its sources of income and standardize procedures for settling accounts tax and this helps in reducing the time, effort and cost of financial authority and the taxpayer and reduce the incidence of tax evasion.